Diagnostic Criteria for Dementia with Lewy Bodies: Updates and Future Directions - Masahito Yamada; Junji Komatsu; Keiko Nakamura; Kenji Sakai; Miharu Samuraki-Yokohama; Kenichi Nakajima; Mitsuhiro Yoshita (Journal of Movement Disorders, 2020)
The aim of this article is to describe the 2017 revised consensus criteria for the clinical diagnosis of dementia with Lewy bodies (DLB) with future directions for the diagnostic criteria. The criteria for the clinical diagnosis of probable and possible DLB were first published as the first consensus report in 1996 and were revised in the third consensus report in 2005. After discussion at the International DLB Conference in Fort Lauderdale, Florida, USA, in 2015, the International DLB Consortium published the fourth consensus report including the revised consensus criteria in 2017. The 2017 revised criteria clearly distinguish between clinical features and diagnostic biomarkers. Significant new information about previously reported aspects of DLB has been incorporated, with increased diagnostic weighting given to rapid eye movement (REM) sleep behavior disorder (RBD) and iodine-123-metaiodobenzylguanidine (MIBG) myocardial scintigraphy. Future directions include the development of the criteria for early diagnosis (prodromal DLB) and the establishment of new biomarkers that directly indicate Lewy-related pathology, including α-synuclein imaging, biopsies of peripheral tissues (skin, etc.) for the demonstration of α-synuclein deposition, and biochemical markers (cerebrospinal fluid/blood), as well as the pathological evaluation of the sensitivity and specificity of the 2017 revised diagnostic criteria. In conclusion, the revised consensus criteria for the clinical diagnosis of DLB were reported with the incorporation of new information about DLB in 2017. Future directions include the development of the criteria for early diagnosis and the establishment of biomarkers directly indicative of Lewy-related pathology.